3095 Perceived Knowledge of Palliative Care among Immigrants: A Secondary Data Analysis from the Health Information National Trends Survey. (27th March 2019) - Barwise, Amelia; Cheville, Andrea; Wieland, Mark; Gajic, Ognjen; Greenberg-Worisek, Alexandra
Abstract : OBJECTIVES/SPECIFIC AIMS: Immigrants to North America receive more interventions at end of life.The reasons for this are not entirely clear but may potentially be due to knowledge gaps. The primary objective of this study was to measure and describe levels of perceived knowledge about palliative care among immigrants to the US compared to those born in the US. Our secondary objective was to identify trusted sources for seeking information about palliative care among immigrants and compare these trusted sources with those born in the US. We hypothesized that immigrants would have less knowledge of palliative care than those born in US and would trust different sources for information about palliative care. METHODS/STUDY POPULATION: We analyzed data from the nationally representative 2018 Health Information National Trends Survey (HINTS 5, cycle 2). Questionnaires were administered via mail between January and May 2018 to a population-based sample of adults. The primary outcome of interest was assessed using the item "How would you describe your level of knowledge about palliative care?" The secondary outcome of interest was determined using the item "Imagine you had a strong need to get information about palliative care, which of the following would you most trust as a source of information about palliative care?" All analyses were complete case analyses and conducted with survey commands using SAS 9.3 (SAS Institute Inc, Cary, NC, USA). Descriptive statistics were calculated, and bivariate analyses run between the outcomes of interest and sociodemographic characteristics (age, sex, education, race/ethnicity, nativity, English language proficiency). Multivariable logistic regressions were conducted to assess the role of nativity, controlling for statistically significant and relevant sociodemographic variables. Jackknife weighting was used to generate population-level estimates. RESULTS/ANTICIPATED RESULTS: The response rate was 33% (n=3384) and included 2846 (85.3% weighted) born in the US and 492 (14.7% weighted) not born in the USA. About 70% of those born in the US and 77% of immigrants (weighted) responded that they had "never heard of palliative care." Trusted sources of palliative care were very similar between the groups (all p > 0.05). Both groups' preferred trusted source of palliative care knowledge was "health care provider, " with over 80% of respondents in each group selecting this option. Printed materials and social media were the least popular trusted sources among both groups. After adjusting for relevant sociodemographic characteristics, we found no association between poor knowledge of palliative care and nativity (p=0.22). Female respondents had 2.5-fold increased odds of reporting low levels of perceived knowledge of palliative care (OR = 2.58, 95% CI = 1.76-3.78; p<0.001). Education was an important predictor of perceived knowledge of palliative care; as education level increased, so did perceived knowledge of palliative care (p < 0.001). DISCUSSION/SIGNIFICANCE OF IMPACT: Perceived knowledge of palliative care is poor generally, regardless of birthplace. Trusted sources for palliative care are similar between immigrants and those born in the US. Education is important and is a strong predictor of perceived knowledge of palliative care. Women perceive they have lower levels of knowledge of PC than men. Differences in end of life care between immigrants and non-immigrants cannot be explained by knowledge differences. Further research is needed to examine the potential factors including suboptimal communication between providers and immigrant patients to understand why these differences are noted. Future strategies for improving knowledge of palliative care should target health care providers as the key trusted source of information to help address deficits noted in this study.